Effect of extrinsic motivation toward the happiness level: a case study of plantation workers at Sime Darby Pantation Kempas Estate / Hafizuddin Hilmi Zulkifli - Zulkifli, Hafizuddin Hilmi (Faculty of Plantation and Agrotechnology, 2018)
Extrinsic motivation is the environmental factor which internally affect the employee’s motivation. Demotivation often caused lower satisfaction productivity of employees. This research was conducted to determine the relationship between effects of extrinsic motivation towards the happiness level of plantation workers and identify the most dominant factors in extrinsic motivation that can influence the happiness level among plantation workers. A survey of 63 workers was carried out to support this study. The independent variables were salary, supervision, and communication towards the dependent variable which is happiness level among plantation workers. There were two important analysis test used: Correlation and Regression Analysis Test. Results from the correlation analysis shows salary, supervision, and communication have significant relationship towards the happiness level of plantation workers with mean of 0.543, 0.799, and 0.335 respectively. The regression analysis shows the supervision factor (β = 0.687) was the most dominant factor influenced the happiness level followed by salary (β = 0.171), and communication (β = 0.155). In conclusion, all the extrinsic motivation factors being studied influenced the happiness level among plantation workers. It was recommended for the company to restructure the communication method in working environment offered to their workers.